The Influence of Principal’s Democratic Leadership Style and Teacher’s Work Discipline on Student’s Learning Outcomes - Panjitiana, Muhammad; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2024)
The purpose of this study was to determine the effect of the Principal’s Democratic Leadership Style and Teacher Work Discipline on Student Learning Outcomes at SMP Muhammadiyah Koba. The sample size taken was 62 teachers education personnel and students at SMP Muhammadiyah Koba, Central Bangka Regency. The sampling technique was purposive sampling, where the respondents taken were teachers and education personnel at SMP Muhammadiyah Koba, Central Bangka Regency. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 75 statement items. The analysis technique used was multiple linear regression analysis. The results showed that there was an influence of the Principal’s Democratic Leadership Style and Teacher Work Discipline on student learning outcomes Second, the influence of the Principal’s Democratic Leadership Style on student learning outcomes Third, the influence of Teacher Work Discipline on student learning outcomes.